First step in implementation of opportunistic salpingectomy for prevention of ovarian cancer: Current care and its determinants. (20th January 2023) - Gelderblom, Malou E.; Jaspers, Veerle; Akkermans, Reinier P.; Slangen, Brigitte; Oei, Angele L. M.; van Ginkel, Alexandra A.; Ngo, Huy; IntHout, Joanna; Hermens, Rosella P. M. G.; de Hullu, Joanne A.; Piek, Jurgen M. J.
Abstract: Introduction: Opportunistic salpingectomy (OS) refers to additional removal of the fallopian tubes during abdominal surgery performed for another medical indication, as prevention for ovarian cancer. As OS has been inconsistently implemented, its clinical practice varies worldwide. To reduce this variation, insight is required into current clinical practice and its determinants. Therefore, the study aim was to determine the implementation of counseling and performance of OS between 2015 and 2018, and its patient, surgical, physician, and hospital characteristics. Material and methods: Retrospective study using electronic medical records from six different Dutch hospitals: two academic, two large teaching, and two non‐teaching hospitals. Patients were considered eligible for OS if they underwent elective non‐obstetric abdominal surgery for a gynecological indication from January 2015 through December 2018. Primary outcomes were uptake of counseling and performance of OS. Multilevel multivariable logistic regression analyses were conducted to identify characteristics associated with OS. Results: A total of 3214 patients underwent elective non‐obstetric abdominal surgery for a gynecological indication and were eligible for OS. Counseling on OS increased significantly from 2.9% in 2015 to 29.4% in 2018. In this period, 440 patients were counseled on OS, of which 95.9% chose OS. Performance of OS increased significantly from 6.9% in 2015 to 44.5% in 2018. Counseling for and performance of OS were more likely in patients who had surgery by laparoscopic approach, were counseled by a gynecological resident, or had more than three contact moments before surgery. Additionally, OS was less likely in patients who had vaginal surgery. Conclusions: Although the uptake of OS increased from 2015 to 2018, the majority of patients who were eligible for OS were not counseled and did not undergo OS. Its clinical practice varies on patient, surgery, and physician characteristics. Therefore, an implementation strategy tailored to associated determinants is recommended. Abstract : Counseling and performance of opportunistic salpingectomy increased significantly from 2015 until 2018 without national recommendations within Dutch hospitals. However, counseling and performance varied greatly, which could be explained by patient, surgical and physician characteristics.